The effect of prenatal action of dexamethasone on morphological changes of the thyroid gland stromal compartment in juvenile rats - Fedosieieva, O. V.; Bushman, V. S.; Федосєєва, Ольга Віталіївна; Бушман, Вікторія Сергіївна (My University, 2021)
The thyroid gland is important for the normal functioning of the body, and is the largest endocrine organ, which among the endocrine glands will be the first in the process of embryogenesis. In recent decades, the prevalence of thyroid pathologies of various origins among the world's population has reached critical proportions. The use of glucocorticoids during pregnancy remains a debatable issue in obstetrics today, as they can both positively and negatively affect the processes of organ morphogenesis and be the cause of pathological conditions in the postnatal period. It is known that the entry of cortisol from mother to fetus through the placenta is controlled by enzymes produced by the latter. However, synthetic glucocorticoids, such as dexamethasone, can freely cross the bloodplacental barrier and cause changes in postnatal immunity and disease in the future. The thyroid gland, having a relatively "simple" basic structure depending on the level of activity and the period of ontogenesis, exhibits various forms of morphological organization. Ideas about the structure and function of the thyroid gland were formed in the course of centuries of its study. Modern experimental and technical capabilities of the study of the body provided information about the structural and functional features of the thyroid gland and the numerical relationships of its structures at different levels of the organization. The aim of the study was to establish the features of the morphogenesis of the rats' thyroid gland from 60 to 120 days of life after prenatal exposure to dexamethasone. Statistical analysis of the results was performed using a personal computer based on the Windows XP operating system using the statistical package "Statistica for Windows 6.0" (StatSoftInc., Serial number №AXXR712D833214FAN5), Excel (Microsoft Office, USA). Methods of variation statistics were used. All research results were recorded in journals and protocols of primary documentation, as well as with the use of electronic media. Significance of differences between groups was assessed using Student-Fisher t-test for a confidence level of at least 95 % (p <0.05). During the study it was found that in the juvenile period the morphological structure of the rats' thyroid gland of intact and control groups is finally formed, in the parts of which the peripheral and central parts with rather high sclerosing index (6.20 and 6.46, respectively) can be icroscopically distinguished due to prevalence. the percentage of parenchymal component (60.82±1.13 % and 61.44±0.71 %) above the stroma (9.86± 1.02 % and 9.53±0.94 %). The study of material obtained from animals prenatally exposed to dexamethasone showed a violation of the morphogenesis of histoarchitectonics of the thyroid gland with the formation of a lobular structure of its particles due to an increase in stromal component (23.63±0.88 %), which was expressed in a decrease in sclerosis index (2.364), but there was a compensatory increase in the percentage of follicular epithelium on the 120th day of life (55.87±0.79 %) compared with the 90th day (49.24± 1.25 %), without morphological signs of functional disorders.
Keywords: thyroid gland; dexamethasone; morphogenesis; experiment; stromal component; rat